Social Service Activity 'Collect Your Waste' Together in Waste Collection on Car Free Day at Slamet Riyadi Solo - Prastowo, Ichwan; Resmi, Prasiwi Citra (Universitas Sahid Surakarta, 2023)
Abstract : The problem of waste has not been completely resolved to date, despite many efforts, especially in large cities like Solo. The Car Free Day (CFD) activity on Slamet Riyadi Solo, which takes place every Sunday, contributes to the waste problem in Solo. The implementation of this community service focuses on collecting waste in the CFD Solo area with the goal of raising awareness among the public about proper waste disposal, making them aware of the dangers of littering, and promoting personal and environmental cleanliness. The method of implementation involves providing guidance to CFD Solo users, collecting waste together according to its type, and disposing of it properly. The approach is to encourage community members to join together in taking responsibility for the cleanliness of the CFD Solo environment. The result of this implementation is the creation of a clean and healthy environment, ensuring that all CFD Solo users feel safe and comfortable. Top of Form Keywords: waste, CFD Solo, clean, healthy, safe, and comfortable